2021
DOI: 10.1111/apha.13642
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in myocardial infarction and heart failure

Abstract: Myocardial infarction (MI) occurs when coronary blood flow is decreased due to an obstruction/occlusion of the vessels, leading to myocardial death and progression to heart failure (HF). Cognitive impairment, anxiety, depression and memory loss are the most frequent mental health problems among patients with HF. The most common cause of cognitive decline is cardiac systolic dysfunction, which leads to reduced cerebral perfusion. Several in vivo and clinical studies provide information regarding the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 97 publications
(293 reference statements)
0
21
0
Order By: Relevance
“…A reduction in cerebral blood flow (CBF) is an inciting event responsible for neuropathology in many diseases, including AMI [ 7 ]. Decreased brain oxygen and glucose supply, as a result of inadequate CBF, causes secondary brain injury, including neuroinflammation, oxidative stress, and cell death [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in cerebral blood flow (CBF) is an inciting event responsible for neuropathology in many diseases, including AMI [ 7 ]. Decreased brain oxygen and glucose supply, as a result of inadequate CBF, causes secondary brain injury, including neuroinflammation, oxidative stress, and cell death [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, necroptosis, and ferroptosis are associated with cognitive impairment in myocardial infarction [ 7 ]. Brain apoptosis was reported in rats with cardiac I/R injury [ 8 , 9 ]; however, the occurrence of brain necroptosis and ferroptosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found that the expressions of Bax in the hippocampal cortex changed female mice with HF, which may affect the apoptosis process of neurons related to cognitive function in the brain ( 84 ). Furthermore, evidence have shown that the expression of caspase family, especially caspase 3 and 6, have been increased in the hippocampal tissue of mice with HF ( 85 ). Animal studies also found that the activation of the RAS in mice with HF can affect AMPK-PGC1α signaling by stimulating angiotensin II receptors and increase the apoptosis of neural stem cells in the hippocampus of rats ( 86 ).…”
Section: Pathophysiology Cellular Mechanism and Risk Factors Of CI In Hfmentioning
confidence: 99%
“…Impaired vascular autoregulation resulting in white matter injury, neurohormonal dysregulation, systemic inflammation, and cerebral microvascular dysfunction may also contribute to generating a state of chronic cerebral hypoxia leading to brain microinfarcts and neurodegeneration ( Adelborg et al, 2017 ). The latter may be enhanced by oxidative stress, dendritic spine loss, glial activation, and programmed cell death ( Jinawong et al, 2021 ).…”
Section: Pathophysiology Of Atrial Cardiopathy-related Cognitive Impa...mentioning
confidence: 99%